Fly-in, fly-out, drive-in, drive-out: The Australian mining boom and its impacts on the local economy. (February 2015) - Perry, Martin; Rowe, James E
A traditional question in local economic development is whether it is better to take work to the workers or workers to the work. The widespread use of fly-in, fly-out (FIFO) or drive-in, drive-out (DIDO) to support Australia's mining industry raises a variant to this question: is it possible to promote regional development without a permanent, resident workforce? FIFO and DIDO have become the predominant ways of providing a permanent operational workforce to the mining industry. It explains why cities such as Perth, Brisbane and Mackay have large populations of mining workers while mining operations are located in remote parts of the country. FIFO brings advantages to mining companies and employees but is generally viewed as antithetical to local economic development: it is accused of eroding the viability of the resource towns that emerged with earlier phases of the mining industry and of generating social problems in both the places where FIFO workers reside permanently and around their temporary work locations. The offsetting advantages appear to provide a strong case for the use of non-resident workers but they arise from the particular context in which mining is occurring rather than being an inherent feature of this form of employment. A case study of the proposed Mt. Todd gold mine located in close proximity to the Northern Territory town of Katherine shows how the potential use of FIFO workers encourages local support for mining operations.